2020
DOI: 10.3390/jcm9072158
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and COVID-19: Oro-Naso-Sensory Perception

Abstract: Through a recent upsurge of severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) pandemic, the clinical assessment of most of the coronavirus disease 19 (COVID-19) patients clearly presents a health condition with the loss of oro-naso-sensory (ONS) perception, responsible for the detection of flavor and savor. These changes include anosmia and dysgeusia. In some cases, these clinical manifestations appear even before the general flu-like symptoms, e.g., sore throat, thoracic oppression and feve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 100 publications
1
17
0
6
Order By: Relevance
“…Furthermore, our results suggest that overweight and obesity could be risk factors for severe infection with COVID-19 in line with emerging data published in other clinical studies (Hamer et al, 2020;Sattar et al, 2020). Indeed, potential mechanisms have been linked to immune hyperresponsiveness, altered metabolic responses and pulmonary dysfunction, including a reduction in forced expiratory volume and a forced biological capacity, to the problem of overweight or obesity (Khan et al, 2020;Sattar et al, 2020). Also, lipid peroxidation is a key factor giving rise to reactive lipid aldehydes which will affect the prognosis of patients infected with SARS-CoV-2 (Demetrios et al, 2020).…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Furthermore, our results suggest that overweight and obesity could be risk factors for severe infection with COVID-19 in line with emerging data published in other clinical studies (Hamer et al, 2020;Sattar et al, 2020). Indeed, potential mechanisms have been linked to immune hyperresponsiveness, altered metabolic responses and pulmonary dysfunction, including a reduction in forced expiratory volume and a forced biological capacity, to the problem of overweight or obesity (Khan et al, 2020;Sattar et al, 2020). Also, lipid peroxidation is a key factor giving rise to reactive lipid aldehydes which will affect the prognosis of patients infected with SARS-CoV-2 (Demetrios et al, 2020).…”
Section: Discussionsupporting
confidence: 88%
“…Likewise, another study COVID-19 patients showed no difference in lymphocyte and D-dimer levels between those with peripheral nervous system disorders with loss of taste and smell as the main symptom and those without these disorders and, therefore, without anosmia or ageusia (Ling et al, 2020). These noticeable alterations in biological parameters including inflammatory (D-dimer) and immune (lymphocytes) indicators in subjects suffering from anosmia and/or ageusia can be attributed to the severity of the clinical symptoms which strongly activate the immune system, leading to a severe inflammatory (Trotier et al, 2007;Khan et al, 2020;Ling et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Existing gustatory and olfactory sensory deficiency due to obesity may mask the viralinduced diminished taste and smell self-reported experiences, leading to a higher portion of undetected cases in this population (21), we need a better understanding of how chemosensory profile changes in patients with obesity. Furthermore, in light of the potential for using oro-naso sensory perception as an early marker of SARS-CoV-2 infection (22)(23)(24), it needs to be assessed whether the predictive relation between the chemosensory loss and COVID-19 illness generalizes to participants with obesity.…”
Section: Despite This Risk Covid-19 Chemosensory Symptoms Have Not Ymentioning
confidence: 99%